Algebraische Zahlentheorie: 12.8. bis 18.8.1979 - Roquette, Peter (Tagungsbericht, 1979)
S. Agou, Villeurbanne; H.-J. Bartels, Göttingen; S. A. Basarab, Heidelberg; E. Becker, Dortmund; H. Benz, Köln; H. Brunotte, Essen; D. J. Bushnell, London; H. Cohn, New York; R. W. Davis, San Diego; M. Eichler, Arlesheim; G. Frei-Imfeld, Sillery; G. Frey, Saarbrücken; W.-D. Geyer, Erlangen; K. Girstmair, Innsbruck; C. Greither, München; F.-P. Heider, Köln; H. Jacobinski, Göteborg; W. Jehne, Köln; E. Kani, Heidelberg; N. Klingen, Köln; K. Lakkis, Thessalonicki; E. Lamprecht, Saarbrücken; H. Lang, Münster; J. B. Leicht, Heidelberg; H.-W. Leopoldt, Karlsruhe; B. Liehl, München; F. Lorenz, Münster; G. Martens, Erlangen; B. H. Matzat, Karlsruhe; M. Neubrand, Bonn; K. Oozeki, Tripoli; Ch. Parry, Blacksburg; R. Perlis, Bonn; M. Peters, Münster; A. Pfister, Mainz; M. Pohst, Köln; A. Prestel, Konstanz; P. Roquette, Heidelberg; A. E. Ross, Worthington; W. Scharlau, Münster; R. Schertz, Köln; A. Schinzel, Warsaw; V. Schulze, Berlin; H. D. Steckel, Köln; H.-J. Stender, Köln; R. J. Stoecker, Rotterdam; Olga Taussky Todd, Pasaden; R. Transier, Heidelberg; St. Turner, Erlangen; R. W. van der Waall, Amsterdam; H. Zassenhaus, Columbus; H. G. Zimmer, Saarbrücken